DXMSMS Match Program for Automated Analysis of LC‐MS/MS Data Obtained Using Isotopically Coded CID‐Cleavable Cross‐Linking Reagents. Issue 1 (12th December 2014) - Petrotchenko, Evgeniy V.; Makepeace, Karl A.T.; Borchers, Christoph H.
Abstract: Cross‐linking combined with mass spectrometry for the study of proteins and protein complexes is greatly facilitated by the use of isotopically coded cleavable cross‐linking reagents. The isotopic coding of the cross‐linker enables confident detection of the cross‐link signals, while cleavage of the cross‐linker provides masses of the individual peptides composing the cross‐link and, therefore, facilitates unambiguous assignment of the cross‐links. Here, we describe the DXMSMS Match program, designed for automatic analysis of LC‐MS/MS mass spectrometric data obtained with isotopically coded CID‐cleavable cross‐linkers. The program verifies the assignments of the cross‐links by precursor mass and by inspection of the MS/MS spectra for the fragments and the cleavage products of the cross‐linked peptides. The program produces nonprobabilistic scores for matching the spectra to the theoretical fragmentation of the cross‐links and a visual interface for the validation of the mass spectral matches. © 2014 by John Wiley & Sons, Inc.